2018
DOI: 10.3389/fpubh.2018.00327
|View full text |Cite
|
Sign up to set email alerts
|

Association of Early Life Exposure to Phthalates With Obesity and Cardiometabolic Traits in Childhood: Sex Specific Associations

Abstract: Few studies have investigated longitudinal associations between early life phthalate exposure and subsequent obesity and cardiovascular risks in children with inconsistent results. We aimed to evaluate the associations between phthalate exposure during gestation and childhood with offspring obesity and cardiometabolic risk factors in 500 mother-child pairs from the Rhea pregnancy cohort in Crete, Greece. Seven phthalate metabolites [monoethyl phthalate (MEP), mono-n-butyl phthalate (MnBP), mono-isobutyl phthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 49 publications
2
37
2
Order By: Relevance
“…Fourth, the long shelf-life of most UPFs increases the risk of contamination from plastic packaging by substances such as bisphenols (which have endocrine-disrupting properties [66]) or phthalates (which are associated with dysregulated sex hormones, obesity, and insulin resistance [67]). A recent study conducted in the US showed that UPF consumption was associated with increased exposure to phthalates [68], which have suggested associations with obesity, especially in children [69]. Lastly, acrylamide, a neo-formed compound created during thermal processing of food as a result of the Maillard reaction, was found to induce adipocyte differentiation and obesity in mice [70].…”
Section: Plos Medicinementioning
confidence: 99%
“…Fourth, the long shelf-life of most UPFs increases the risk of contamination from plastic packaging by substances such as bisphenols (which have endocrine-disrupting properties [66]) or phthalates (which are associated with dysregulated sex hormones, obesity, and insulin resistance [67]). A recent study conducted in the US showed that UPF consumption was associated with increased exposure to phthalates [68], which have suggested associations with obesity, especially in children [69]. Lastly, acrylamide, a neo-formed compound created during thermal processing of food as a result of the Maillard reaction, was found to induce adipocyte differentiation and obesity in mice [70].…”
Section: Plos Medicinementioning
confidence: 99%
“…Early-life exposures might have different effects in male and female biology, and the influence of possible confounders such as age at menarche might also be different for men and women. 43,44 Male and female puberty might differ in terms of behavior, hormonal factors, and changes in body composition. Both men and women put in fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…The downstream effects of maternal DEHP exposure on the developing fetus remain less clear. Valvi et al and Vafeiadi et al have reported that maternal DEHP exposure is associated with a decrease in systolic blood pressure in children aged <7 years (Vafeiadi et al, 2018; Valvi et al, 2015). Similarly, Sol et al reported that maternal phthalate exposure was associated with a decrease in systolic and diastolic blood pressure in girls, but not boys (mean age 9.7 years) (Sol et al, 2020).…”
Section: Di‐2‐ethylhexyl Phthalatementioning
confidence: 99%